Core sampler at Brechin Castle - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
This is the core sampler at Brechin Castle Factory.
Cataloger's title
Keywords: Sugar machinery -- Trinidad and Tobago; Sugar factories -- Trinidad and Tobago